2018
DOI: 10.21475/ajcs.18.12.06.pne1086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical thinning using 6-benzyladenine (BA) on Maciel peach (Prunus persica L.)

Abstract: High effective peach fruit set results in an excessive amount of fruits, requiring thinning accomplishment, which is a manual practice and demands specialized labor, raising production costs. In this sense, chemical thinning may be an alternative to improve the peach production chain. The objective of this work was to evaluate the efficiency of 6-benzyladenine (BA) on chemical thinning and the effect of different BA dosages on peach production and color characteristics of 'Maciel' fruits. Treatments consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Peach tree cultivars exhibit high bloom, a fact that results in an excessive number of fruits which is incompatible with the production capacity of the plant (Giovanaz et al, 2016;Barreto et al, 2018). The excessive number of fruits leads to small fruits that have low commercial value (Giovanaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peach tree cultivars exhibit high bloom, a fact that results in an excessive number of fruits which is incompatible with the production capacity of the plant (Giovanaz et al, 2016;Barreto et al, 2018). The excessive number of fruits leads to small fruits that have low commercial value (Giovanaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, few have shown satisfactory thinning effects. In order to carry out chemical thinning of peach trees, some products, such as 6-benzyladenine, gibberellins, ethylene and metamitron (Meitei et al, 2013;Giovanaz et al, 2014;Giovanaz et al, 2016;Farias et al, 2017;Barreto et al, 2018), have been investigated. Metamitron may be an efficient alternative to peach tree thinning (McArtney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the difference in bioactive compounds in the fruits between harvests, the peach cultivar may also be associated. Differences between metamitron doses and harvests have been reported for cultivars BRS Kampai (Farias et al, 2019a), Maciel (Barreto et al, 2018a) and Sensação (Farias et al, 2017).…”
Section: Continuationmentioning
confidence: 93%
“…Regardless of the dose, metamitron reduced antioxidant activity in the peaches in 2016 (Table 4). It is suggested that this reduction may be due to the use of metamitron in association with the dose (Barreto et al, 2018a;Farias et al, 2019a) and/or time of application (Farias et al, 2017). In both harvests, the unthinned trees obtained similar antioxidant activity values when compared with the trees subjected to the hand thinning of fruits.…”
Section: Continuationmentioning
confidence: 99%
See 1 more Smart Citation